The influence of workplace happiness and innovative work behavior on job satisfaction mediated by work engagement - Rosdaniati Rosdaniati (Ümit Hacıoğlu, 2021)
The purpose of this study is to examine and analyze the influence of workplace happiness and innovative work behavior on job satisfaction mediated by work engagement on employees of a private university in Tenggarong, East Kalimantan during the Covid-19 pandemic. This research is quantitative with a sample of 100 people taken through proportional stratified random sampling. The data analysis technique used is descriptive statistical analysis and structural equation modeling (SEM). The conclusion of this study is that there is a positive influence between workplace happiness and innovative work behavior on job satisfaction, there is a positive influence between workplace happiness and work engagement, there is a positive influence between work engagement and job satisfaction, and there is a positive influence between workplace happiness on job satisfaction mediated by work engagement.